2017
DOI: 10.1186/s12940-017-0330-5
|View full text |Cite
|
Sign up to set email alerts
|

Road traffic noise and registry based use of sleep medication

Abstract: BackgroundRoad traffic noise has been associated with adverse health effects including sleep disturbances. Use of sleep medication as an indicator of sleeping problems has rarely been explored in studies of the effects of traffic noise. Furthermore, using registry data on sleep medications provides an opportunity to study the effects of noise on sleep where attribution of sleep problems to noise is not possible.MethodsWe used questionnaire data from the population-based study Health and Environment in Oslo (HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…After removing duplicate records, we screened the titles and abstracts of the remaining 907 records and further excluded 877 that were deemed irrelevant, leaving us with 30 full texts for in-depth review. One of them [22] did not report results for anxiolytic or antidepressant use, rather it had combined psychotropic medication use as the outcome; the outcome in the study by Bocquier et al [21] was combined anxiolytic–hypnotic medication intake; and others had general psychological distress [23,51], quality of life [52,53], or sleep/hypnotic medication use [54,55] as the outcome. In two studies, the exposure considered was noise annoyance [56,57].…”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicate records, we screened the titles and abstracts of the remaining 907 records and further excluded 877 that were deemed irrelevant, leaving us with 30 full texts for in-depth review. One of them [22] did not report results for anxiolytic or antidepressant use, rather it had combined psychotropic medication use as the outcome; the outcome in the study by Bocquier et al [21] was combined anxiolytic–hypnotic medication intake; and others had general psychological distress [23,51], quality of life [52,53], or sleep/hypnotic medication use [54,55] as the outcome. In two studies, the exposure considered was noise annoyance [56,57].…”
Section: Resultsmentioning
confidence: 99%
“…Causal diagrams were available for 144 (62%) articles. Sixty (42% of those with one or more diagrams available) included the diagram in the manuscript directly, 81 (56%) in supplementary online material, one (<1%) provided the diagram on request (Bliddal et al 2016) 22 one (<1%) provided a link to the diagram on www.dagitty.net (Evandt et al 2017A), 23 and one (<1%) referred to a diagram from a previous publication (Buchner & Rehfuess 2015). 24 No diagram was available for 90 (38%) articles, including four (1%) articles that referred to supplementary online materials that were unavailable, one article where the diagram was missing from supplementary material, one (<1%) where the printed figure was incorrect, and one (<1%) that provided invalid weblinks to www.dagitty.net .…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have attempted to extend the noise sources to include traffic noise from roads and railways as well [ 31 , 32 , 33 , 34 , 35 ]. In particular, much research has investigated road traffic noise in different contexts and its correlation with population’s health and wellbeing [ 36 , 37 ]. Studies have shown that higher exposure to road traffic noise could significantly increase annoyance and have harmful effects on people’s sleep quality, wellbeing and other health outcomes [ 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%